Bokrecension: Strengthening Teaching and Learning in Research Universities. Strategies and Initiatives for Institutional Change - Axelsson, Svante (Högre utbildning, 2018)
Svante Axelsson om Bjørn Stensaker, Graham T. Bilbow, Lori Breslow & Rob van der Vaart (Eds.). Strengthening Teaching and Learning in Research Universities. Strategies and Initiatives for Institutional Change. Palgrave Macmillan, 2017, 228 p.